Larval morphology of Lebertia insignis Neuman, 1880, L. porosa Thor, 1900 and L. saxonica Thor, 1911 (Acari, Hydrachnidia: Lebertiidae) - Tuzovskij, Petr V. (Zootaxa, 2016)
Illustrated redescriptions of the larvae of the water mite species Lebertia insignis Neuman, 1880, L. porosa Thor, 1900 and L. saxonica Thor, 1911 are presented. The present data suggest that L. saxonica, recently considered as a subspecies or a junior synonym of L. insignis, or as a “species incerta“ should be recognized as separate species. A key to all named species based on larvae is given.